(untitled) (SAARC Journal of Agriculture, 2015)
To investigate the effect of dietary mulberry leaf meal on body weight, feed conversion efficiency and blood cholesterol level, 240 day-old broiler chicks (Cobb 500) were divided into 6 treatments, each with 4 replications (10 birds/ per replicate) and offered manually prepared diets supplemented with 2.5, 3.5, 4.5% mulberry leaf meal (MLM), MLM Extract and 0.5% for a period of six weeks. Average body weight (g) gain increased (P> 0.05) at 2.5 or 4.5% supplementation of MLM and with MLM extract compared to control and antibiotic group. Feed conversion ratio was better at 4.5% supplementation (1.67) and on addition of MLM extract (1.63) compare to control (1.79). Total cholesterol, HDLcholesterol and triglyceride of broiler chicks in different dietary treatments of during experimental periods were non-significant at day 10 to 15 but total cholesterol and triglyceride decreased significantly (P>0.05) at d 15 to 22 compared to control and antibiotic group. Significant (P<0.05) reduction of total cholesterol and triglyceride with supplementation of mulberry leaf meal at 2.5, 3.5, 4.5% MLM, MLM extract were also observed at d 22 to 42 compared to control and antibiotic group. The result suggests that inclusion of mulberry leaf meal (both 3.5% powder and extract) may be used to formulate low-cost broiler grower diet in order to produce low-cholesterol broiler meat. DOI: http://dx.doi.org/10.3329/sja.v12i2.21920 SAARC J. Agri., 12(2): 79-89 (2014)